Neanderthals on the Lower Danube: Middle Palaeolithic evidence in the Danube Gorges of the Balkans. (25th August 2021) - Borić, Dušan; Cristiani, Emanuela; Hopkins, Rachel; Schwenninger, Jean‐Luc; Gerometta, Katarina; French, Charly A. I.; Mutri, Giuseppina; Ćalić, Jelena; Dimitrijević, Vesna; Marín‐Arroyo, Ana B.; Jones, Jennifer R.; Stevens, Rhiannon; et al.
Abstract: The article presents evidence about the Middle Palaeolithic and Middle to Upper Palaeolithic transition interval in the karst area of the Danube Gorges in the Lower Danube Basin. We review the extant data and present new evidence from two recently investigated sites found on the Serbian side of the Danube River – Tabula Traiana and Dubočka‐Kozja caves. The two sites have yielded layers dating to both the Middle and Upper Palaeolithic and have been investigated by the application of modern standards of excavation and recovery along with a suite of state‐of‐the‐art analytical procedures. The presentation focuses on micromorphological analyses of the caves' sediments, characterisation of cryptotephra, a suite of new radiometric dates (accelerator mass spectrometry and optically stimulated luminescence) as well as proteomics (zooarchaeology by mass spectrometry) and stable isotope data in discerning patterns of human occupation of these locales over the long term.